ON THE DEVELOPMENT TENDENCIES OF MODERN SOCIETY AND EDUCATION - Rozieva Komila Ernazarovna (American Journals, 2023)
The education of the 21st century is connected with globalization, digitalization, rapid economic development and changes in their processes, requiring many new highly qualified professional personnel.